Relato de mães sobre o diálogo acerca da saúde sexual e reprodutiva com suas filhas adolescentes - Gubert, Fabiane do Amaral (2008)
Qualitative study having as subject, the communication between mothers and adolescent daughters in the family context. Objectives 1. Know, based on experience with mothers of adolescents, their views and experiences on issues related to gender, sexuality and reproduction, the dialogue between mothers and daughters. 2. Identify the mothers´ difficulties/ potentialities, with support in their lived experiences.3. Discover the processes of communication between mothers and daughters, made collectively through dialogue, negotiation and argumentation.4. Propose the practice of Health Education as a mediator of communication between mothers and daughters in the family context. Methodology: The social agents of the research were seven mothers of female adolescents, participants from non-governmental organization Acartes, residents in the District of Pirambu in Fortaleza-CE. The theoretical framework used was the Theory of Diversity and Universality of the Care of Madeleine Leininger. Data collection followed the model Observation-Participation Reflection, proposed by Leininger; semi-structured interviews and eleven meetings with the group, addressing the stages of development of the daughters: birth, childhood, puberty and adolescence. The project was submitted and approved by the Ethics Committee of the UFC under Protocol No 17/08. Results: social and cultural factors in the community contribute to the vision of sexuality of women and make difficult the dialogue with their daughters. The early pregnancy is a factor in their story of life, and when they project this fact to their daughters, the pregnancy has already occurred, or report that their daughters are likely to become pregnant early. That experience, the fruit of social development, creates barriers, which, alone, women can not overcome, and what happens is the continuation of a cycle in which the relationship of non-dialogue between mother and daughter are reproduced over the generations. In this reality, many times women, placed in a particular cultural background, have little or no degree of motivation of the family or community. When they remember their experiences of adolescence, feelings such as fear and shame are reported in adulthood and relate these feelings as still present in their lives. In relation to dialogue with their daughters, the argument is used by the pregnancy issue, linking it to the future of these barriers in life. For STD, are little discussed as an argument for prevention, not on explaining signs and symptoms, making the vision of adolescents at the preventive issue. The TV is seen as an area that provides the reasoning and negotiation. Conclusions: The study may prompt a renewed vision in the field of sexual and reproductive health in the family, which considers the relational dimension of sexuality, sex and reproduction, aiming to contribute to the promotion of the dialogue between mother and daughter. The intervention of the nurse as part of the team of Health of the Family through the Health Education helps to improve self-esteem and perception of the women´s world, encouraging them to a greater degree of autonomy and power to decide about questions related to sexuality. The reflection of the experiences through the memories of the life cycle can encourage them to think about new projects for their lives and shows that even with difficulties, the dialogue between mothers and daughters can occur, whereas it is never too late to learn